Proposta conceitual de zoneamento ecológico-econômico para o Município de Frederico Westphalen -RS - Missio, Eloir (Universidade Federal de São Carlos, 2003)
At the actual moment on What ecology supportable concerned to the diferent ecossistems depend on the balance between the environment and the development, this research has as a goal to realize the characterization, analyse and elaborate an ecological-economic zoning conceptual proposition to the Frederico Westphalen municipality, state of Rio Grande do Sul, Brazil, adapting to a feasible methodology: a methodology founded on the use of the Geography Information Systems GIS, to elaborate a georeferenced digital data base which allow to understand the structure and the functioning of the natural systems, on purpose of a management supported on the natural borough resources. The borough environment characterization and zoning which present, nearby 262 km2 and 26.759 inhabitants were developed based on topography maps DSG and digital satellite images. The results embody to elaborate maps that refer to the structural landscape elements and to some environmental impact risks, while to the definition and analyse of handled zones proposed the thematic digital maps were overlap using the Analysis of Crossed Impact based on presupposed existence of interrelation of future events and the Intuitive Logic Analyse. This procedure permits to divide the borough area in five zones that present the degree of distinguished environmental fragility. The zones are: the greater environmental frail relative zone ZMAF; average environmental frail relative zone ZMEF; the greater environmental stability relative one ZMAE; urban zone ZMRB and urban expansion zone ZEUR. ZMAF and ZMEF zones take the greatest part of the borough 45,l8% and 36,25% respectively. Based on the problems, potentialities and limitations analyse, it was possible spatialyse the evolution of the environmental degradation process concerned with the use of the natural resources coming from the main economic activities and, based on this analyse, identifying the economic tendency of the region by the economic production of the conflicts using the life population conditions, directioning to a desire way. The methodology used allowed to fix up guidelines into two degrees: one of them is the general covering to all the zones that embody the borough (general guidelines) and, another directed to each managed zone proposed (specific guidelines). Both the general guidelines as the specific ones were elaborated based on criterions and principles established on the diagnosis of the current situation and has as a goal to the natural characteristics of each area while the potentialities are priority.
Keywords: Ecologia; Zoneamento ambiental; Zoneamento ecológico-econômico; Avaliação de riscos ambientais; Sistemas de Informação Geográfica; CIENCIAS BIOLOGICAS